The palace at the end of the sea : a novel - Tolkien, Simon, 1959- (Theo Sterling, 2025)
A young man comes of age and crosses continents in search of an identity -- and a cause -- at the dawn of the Spanish Civil War in a thrilling, timely, and emotional historical saga. New York City, 1929. Young Theo Sterling's world begins to unravel as the Great Depression exerts its icy grip. He finds it hard to relate to his parents: His father, a Jewish self-made businessman, refuses to give up on the American dream, and his mother, a refugee from religious persecution in Mexico, holds fast to her Catholic faith. When disaster strikes the family, Theo must learn who he is. A charismatic school friend and a firebrand girl inspire him to believe he can fight Fascism and change the world, but each rebellion comes at a higher price, forcing Theo to question these ideologies too. From New York's Lower East Side to an English boarding school to an Andalusian village in the foothills of the Sierra Nevada, Theo's harrowing journey from boy to man is set against a backdrop of societies torn apart from within, teetering on the edge of a terrible war to which Theo is compulsively drawn like a moth to a flame.